Multiscale universal interface v2.0: Lowering barriers to scalable multiphysics coupling - Wendi Liu; Omar Ahmed Mahfoze; Mayank Kumar; Stephen M Longshaw; Eduardo Ramos Fernandez; David R. Emerson (Computer Physics Communications, 2026)

Preclinical evaluation of route-dependent immune responses following repeated administration of a Klebsiella pneumoniae lytic phage cocktail in rats - Sonam Rastogi; Mayank Gangwar; Sudhir Kumar Singh; Alka Shukla; Digvijay Singh; Vandana Rastogi; Deepak Kumar; Pooja Sachdeva; Gopal Nath (Molecular Biology Reports, 2026)

Regulation of mitochondrial fission by Drp1 in cardiomyopathy: possible mechanisms linking cellular processes to cell death - Nandini Dubey; Pranav Panchbhai; Gauri Chaturvedi; Satnam Singh; Ahsas Goyal; Neeraj Parakh; Rajiv Narang; Sudhir Kumar Arava; Arvind Kumar; Mayank Yadav; Harlokesh Narayan Yadav (Molecular Biology Reports, 2026)

Therapeutic potential of sulforaphane in neurodegenerative diseases: mechanistic Insights into Nrf2, NF-κB, TrkB, SIRT1, MAPK, and JAK/STAT signalling pathways - Omkar Kumar Kuwar; Sandip Tejpal; Vipul Sharma; Akash Sharma; Aayush Rao; Mayank Attri; Pallavi; Mamta Sachdeva Dhingra (Molecular Biology Reports, 2026)

The interplay between inflammation and oxidative stress in depression: pathogenic mechanisms and treatment approaches - Omkar Kumar Kuwar; Mamta Sachdeva Dhingra; Ayushi Maloo; Tejinder Singh; Inderjeet Singh; Lavish Kumar; Mayank Attri (Molecular Biology Reports, 2026)

Artificial intelligence–driven air quality mapping and forecasting for extreme PM2.5 events - Kuldeep Singh Rautela; Mayank Upadhyay; Manish Kumar Goyal; Sitaram Taigor (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Projected climate change and its influence on watershed hydrology: A case study of Suketi watershed, Himachal Pradesh - Mayank Upadhyay; Ajanta Goswami; Praveen Kumar Thakur; Pankaj Dhote (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Alder-mediated changes in soil properties and microbial activity with implications for ecological succession in temperate Himalayan forests - Shailendra Kumar; Mayank Krishna; Madhur D. Gajbhiye; Satish Chandra Garkoti (Rhizosphere, 2026)

Machine learning and AHP approaches for evaluating land degradation in coal mining landscape - Alka Mishra; Mayank Pandey; Singam L. Swamy; Tarun Kumar Thakur; Achyut Sharma; James T. Anderson; Amit Kumar; Rupesh Kumar (Journal of Geochemical Exploration, 2026)

Field evaluation of polished desalinated produced water for alfalfa irrigation in a semi-arid environment - Teja Saddapalli; Anita Kumari; Dinesh Kumar Saini; Pankaj Trivedi; Mayank Pratap Singh Bangari; Adrianne Lopez; W. Shane Walker; S. M. Impa; S. V. Krishna Jagadish (Irrigation Science, 2026)
Water scarcity is a critical challenge in West Texas, where agriculture and the oil and gas industry compete for limited water resources. The oil and gas industry generates approximately 32% of the nation’s produced water, presenting significant opportunities for beneficial reuse. This study evaluated polished desalinated produced water (PDPW) as a supplemental irrigation source for field-grown alfalfa in a semi-arid region, with conventional groundwater serving as the reference irrigation source. Soil chemistry, heavy metal accumulation, plant physiology, forage quality, and microbial community dynamics were assessed under both irrigation treatments at two growth stages. Polished desalinated produced water met most irrigation water quality standards, although strontium concentrations exceeded recommended thresholds, highlighting the need for continued monitoring. Exceedances in soil macronutrients and organic compounds were primarily attributed to historical soil conditions rather than PDPW application. Interpretation of sodium accumulation was limited because PDPW was blended with groundwater during part of the study period. No significant differences ( p > 0.05) were observed in plant growth or biomass between PDPW and control treatments. Forage quality was comparable and, in some cases, improved under PDPW irrigation through lower fiber concentrations. Microbial community profiling using 16 S and ITS rRNA sequencing revealed stable alpha and beta diversity, with variation driven primarily by sample type and growth stage rather than irrigation source. Dominant bacterial and fungal taxa remained consistent across treatments. These findings suggest that, with appropriate treatment and monitoring, PDPW has the potential to serve as an alternative irrigation source for alfalfa production in semi-arid regions. However, long-term studies are needed to evaluate sustainability and potential cumulative impacts on soil, plants, and microbial communities.

Chronic Fluoride Exposure Disrupts Calcium-Dependent Neurodevelopmental Signalling and Brain Proteomic Architecture: Multi-Target Modulation by Naringin - Ravindra Shantakumar Swamy; Shalini Choudhary; Abhishek Ambawatiya; Vishal Chhabra; Mayank Mishra; Md Abubakar; Smita Shenoy; Naveen Kumar; Rahul L. Gajbhiye; Amita Rai; Velayutham Ravichandiran; Nitesh Kumar (Biological Trace Element Research, 2026)

Integrated N-acetylcysteine-microbial based phytostabilization mitigates lead (Pb) contamination and limits its uptake in wheat (Triticum aestivum L.) grains - Aanand Kumar; Mayank Bhaskar; Akhil Pandey; Radha Rani (Environmental Research, 2026)

Ambient black carbon and its dependence on in situ stubble burning - Vikas Goel; Ajit Kumar; Anjanay Pandey; Mohd Faisal; Umer Ali; Rakesh Maity; Ravindra Khaiwal; Suman Mor; Vikram Singh; Mayank Kumar (Environmental Monitoring and Assessment, 2026)

Fish-inspired locomotion in robotics: Biology, hydrodynamics, and machine learning - Ashish Sharma; Mayank Kumar Singh; Deepak Sachan; Jagadeesh Kadiyam (Ocean Engineering, 2026)

Road dust emission assessment and elemental characterization in a non-attainment city: a case study of Ujjain, Madhya Pradesh, India - Vineet Kushwaha; Mayank Upadhyay; Anil Kumar Sharma (Environmental Monitoring and Assessment, 2026)

Association of Haematological and Biochemical Inflammatory Indices with Angiographic Severity of Coronary Artery Disease in Chronic Stable Angina - Kuldeep Kumar Gaur; Ankit Kumar Yadav; Sojit Tomo; Mayank Yadav; Atul Kaushik; Rahul Choudhary; Surender Deora (Indian Journal of Clinical Biochemistry, 2026)

α-Klotho as a central integrative signalling hub in cognitive function and neuroprotection in neurodegenerative diseases - Priya Bindal; Omkar Kumar Kuwar; Vivek Kumar Singh; Mayank Attri; Pallavi; Sandip Tejpal (Metabolic Brain Disease, 2026)

Antidiabetic effects of Tipuana tipu leaves: in silico docking and experimental study in streptozotocin-induced diabetic rats - Anuragini Kumari; Yogesh Murti; Anuj Kumar Sharma; Km. Pratiksha; Akash Ved; Karuna Shanker Shukla; Mayank Kulshreshtha (In Silico Pharmacology, 2026)

Computational investigation of structural and functional impacts of L163G and W235K mutations in LRR-PGIP of Raphanus sativus: insights into host–pathogen interaction dynamics - Soumya Sharma; Mayank Rashmi; Mahender Kumar Singh; Sarika Sahu; Raja Shankar; Anurag Chaurasia; Girish Kumar Jha; Sunil Kumar (Journal of Plant Biochemistry and Biotechnology, 2026)

Population structure, genetic diversity, and identification of high-yielding stable rice genotypes from north-eastern India using AMMI and MGIDI analyses - Amit Kumar; Riya Raj; C. Balakrishnan; Harendra Verma; W. S. Philanim; Veerendra Kumar Verma; Simardeep Kaur; N. Umakanta; Mayank Rai; S. P. Das (Journal of Crop Science and Biotechnology, 2026)

Unpacking the Drivers of Circular Economy in Tourism: An Interpretive Structural Modeling and Argumentative Discourse Analysis - Mayank Pathak; Pinosh Kumar Hajoary; Jose Arturo Garza-Reyes (Circular Economy and Sustainability, 2026)

Genetic Diversity, Combining Ability and Stability Analysis of Linseed (Linum Usitatissimum) Under Acidic Soil Conditions in the North-Eastern Region of India - M. Bezil; P. Magudeeswari; Malemnganbi Keisham; Abhilash Behera; Amit Kumar; Wricha Tyagi; Mayank Rai (Agricultural Research, 2026)

Variation of Atmospheric Properties over the Central Himalaya During a Low-Intensity Dust Episode: Insights from Lidar and Auxiliary Observations - Shishir Kumar Singh; Narendra Singh; Ashish Kumar; Subhajit Debnath; Mayank Kumar Chauhan; Vikas Rawat; Chandra Prakash; Jayshreekar Pant; B. Krishna Reddy (Aerosol Science and Engineering, 2026)

Synergistic mitigation of lead [Pb(II)] stress in Triticum aestivum L. by heavy metal-tolerant plant growth-promoting (HMT-PGP) microbes and N-acetylcysteine (NAC) - Aanand Kumar; Mayank Bhaskar; Radha Rani (Plant Cell Reports, 2026)

Signatures of Oncosomes as dual-function nanocarriers in targeted drug delivery and early cancer detection - Popat Mohite; Nobendu Mukerjee; Abhijeet Puri; Subham Sarkar; M.M. Rekha; Mayank Kundlas; Mukesh Kumari; Rohit Sharma; Nanasaheb D. Thorat; Parshant Kumar Sharma (Chemical Engineering Journal, 2026)

Modulating drug response through the gut microbiome: pathways to precision therapy - Nitish Kumar; Joy Das; Murugesan Vanangamudi; Naheed Mojgani; Anas Islam; Sathvik Belagodu Sridhar; Himanshu Sharma; Sanjesh Kumar; Uttam Prasad Panigrahy; Shubhrajit Mantry; Mayank Sharma; Mohhammad Ramzan; et al. (Archives of Microbiology, 2026)

Doxorubicin-Induced Cardiotoxicity: Molecular Mechanisms to Novel Therapeutic Frontiers of Recent Preclinical Discoveries - Nandini Dubey; Satnam Singh; Pranav Panchbhai; Gauri Chaturvedi; Ahsas Goyal; Nirmal Singh; Jagriti Bhatia; Rajkumar Yadav; Sudhir Kumar Arava; Arvind Kumar; Mayank Yadav; Abhishek Yadav; et al. (Cell Biochemistry and Biophysics, 2026)

Integrative approaches of plant growth-promoting microbes, CRISPR/Cas gene editing, and AI/ML technologies for abiotic stress alleviation and support climate-resilient agriculture: A review - Aanand Kumar; Mayank Bhaskar; Anamika Kushwaha; Anupam Rawat; Radha Rani (Plant Gene, 2026)

Ecosystem-based assessment of tropical Lobster Sea cage farming impact: A novel BACI-framework for sustainable mariculture expansion along the Northeast coast of Arabian Sea - Mayur Shivdas Tade; Suresh Kumar Mojjada; Abdul Azeez Pokkathappada; Prachi Siddharth Bagde; T.S. Ramshad; Mayank Soni; Aarsha Subramanian; Swathi Lekshmi Perumal Sundaram; Boby Ignatius; Suresh Vettath Raghavan; Achamveetil Gopalakrishnan; Damodaran Nair Divu (Aquaculture, 2026)

Targeted mutagenesis in glutamine synthetase for improved herbicide resistance and nitrogen utilization in maize - Sneha Murmu; Mayank Rashmi; Santosh Kumar Behera; Sunil Kumar; Girish Kumar Jha; Jyoti Kumari; Gyan Prakash Mishra; P.V. Vara Prasad (Biocatalysis and Agricultural Biotechnology, 2026)

Understanding the influence of landcover on spring dynamics and evaporation, in Himalayan region, using stable isotope and discharge - Neeraj Pant; Dharmappa Hagare; Basant Maheshwari; Shive Prakash Rai; Abhinav Patel; Nijesh Puthiyottil; Sharad Kumar Jain; Lakhi Narayan Sahu; Sumit Sen; Mayank Upadhyay (Science of The Total Environment, 2026)

Filtered diesel exhaust via whole body exposure disrupts male reproductive function through dysregulated endocrine axis and subdued testicular GSTs in juvenile Wistar rats - Swarnabha Sarkar; Aditya Dontham; Ravindran Revand; Abhishek Kandpal; Debabrata Dasgupta; Bahni Ray; Mayank Kumar; Asmita Patil (Environmental Toxicology and Pharmacology, 2026)

The KEAP1-Cullin3-RBX1-Nrf2 Axis in Redox Homeostasis: Molecular Mechanisms, Pathophysiological Roles, and Precision Therapeutic Opportunities - Mayank Attri; Omkar Kumar Kuwar (Molecular Neurobiology, 2026)

Deciphering Genetic Variability and Marker-Trait Associations in Rice Genotypes for Low P and High Al Toxicity Stresses Under the Mid-Hill Ecologies of North-Eastern India - C. Balakrishnan; Amit Kumar; Riya Raj; Veerendra Kumar Verma; Simardeep Kaur; Mayank Rai; S. P. Das; Vinay Kumar Mishra (Plant Molecular Biology Reporter, 2025)

Molecular signatures that translate across omics layers and crops under high aluminium and low phosphorus stress facilitate the identification of reliable molecular targets for genotyping in lentil - Kavya Kadiyala; Noren Singh Konjengbam; James M; Mayank Rai; Wricha Tyagi; Ajay Kumar Mahato (Functional & Integrative Genomics, 2025)

Embedding Circular Economy and Sustainability in Tourism Policy: An Institutional Theory Perspective - Mayank Pathak; Sujan Mondal; Pinosh Kumar Hajoary (Circular Economy and Sustainability, 2025)

Molecular insights into GnRH3-associated peptide structure and reproductive responses in Channa striata stimulated with sGnRH analogue - Prachi Asgolkar; Kiran D. Rasal; Rajesh Kumar; Uday Udit; Arvind Sonwane; Manoj Brahmane; Sunil Kumar; Mayank Rashmi; Girish Kumar Jha; Jitendra Kumar Sundaray; Megha Bedekar; Mukunda Goswami (Aquaculture International, 2025)

Air Quality Status and Estimated Health Exposure in Major Metropolitan Indian Cities - Kanak Sharma; Mayank Goyal; Rajeev Kumar Mishra; Thangamani Vijayakumar; Prashant Kumar; Kanagaraj Rajagopal (Aerosol Science and Engineering, 2025)

Targeting thymidylate kinase of Mycoplasma genitalium with phytochemicals: insights from molecular docking and dynamics studies - Krishnendu Barik; Mayank Kumar; Praffulla Kumar Arya; Anil Kumar (In Silico Pharmacology, 2025)

A campaign-based study on the physio-chemical characterization and source apportionment of particulate matter in the Central Himalayas - Vikas Rawat; Narendra Singh; Surendra K. Dhaka; Prashant K. Chauhan; Jagdish C. Kuniyal; Prity S. Pippal; Sanjeev Kimothi; Mayank Kumar Chauhan (Environmental Science and Pollution Research, 2025)

Experimental determination of optimum tire chips-aggregates mixture in combi-grid encased granular piles in soft soil under cyclic loading - N. Muni Pradeep; Suresh Kumar; Sanjoli Gupta; Mayank Nishant (Soil Dynamics and Earthquake Engineering, 2025)

Deciphering the potential Zea nicaraguensis for addressing yield plateau in maize - Priya Garkoti; Velmurugan Senthilkumar; Thotla Naresh; Sachin Prakash; T. V. Anirudh; Mayank Tiwari; Kamlesh Kumar; Narendra Kumar Singh (Genetic Resources and Crop Evolution, 2025)

Tree‐Ring‐Based Drought Reconstruction Reveals Increased Pre‐Monsoon Droughts Over the Past Two Centuries in the Lug Valley Kullu, Northwest Himalayas - Devi Lal; Pushpendra Pandey; Mayank Shekhar; Pritam Chand; Rupesh Dhyani; Ishtiaq Ahmed; Rinku Kumar; Amalava Bhattacharyya; Parminder Singh Ranhotra (International Journal of Climatology, 2025)
Understanding of long‐term drought variability in the Himalayan region is crucial for sustainable water resource management and climate adaptation. We analysed the self‐calibrated Palmer Drought Severity Index (scPDSI) based on a well‐established “signal‐free” standardised tree‐ring width (TRW) chronology of Cedrus deodara (Roxb. ex D.Don) G.Don (deodar) from Lug Valley of Kullu district of Himachal Pradesh, Northwest Himalayas. Tree growth climate analysis indicated that the pre‐monsoon precipitation and the scPDSI positively affected the radial growth, whereas temperature had a negative influence. The strongest correlation between the scPDSI and TRW chronology ( r = 0.636, p n = 114) during the March, April, and May (MAM) period indicates that the pre‐monsoon drought scPDSI‐MAM is the dominant growth‐limiting factor. Using a linear regression model, we reconstructed drought variability back to 1793 ce , explaining 40.5% of the total variance. The reconstruction identified prolonged drought periods (1794–1825, 1888–1980, and 2000–2010) with increasing frequency and intensity in recent decades, while pluvial conditions prevailed during 1825 to 1875 and 1982 to 1998. The multi‐taper method spectral analysis identified the presence of both low and high frequency cycles of 80, 33, 6, 2.3, and 2 years within the reconstructed time series, indicating periodic climatic variability. Spatial correlation with tropical sea surface temperatures indicates strong teleconnections with global climate drivers like the El Niño–Southern Oscillation, Pacific Decadal Oscillation, and Atlantic Multidecadal Oscillation. These findings underscore the rising threat of pre‐monsoon droughts to regional hydrology, agriculture, and socio‐economic stability. As droughts become more frequent, proactive policies and adaptive strategies are essential to minimise future risks acorss this region.

Integration of fluid-invasive, scattering, and imaging methods in resolving pore structures in coal and shale - Shubham Kumar; Debanjan Chandra; Bodhisatwa Hazra; Vikram Vishal; Pathegama Gamage Ranjith; Anwesa Das; Mayank Ahuja; Sayan Ghosh (Fuel, 2025)

Circular RNAs: driving forces behind chemoresistance and immune evasion in bladder cancer - Mohamed J. Saadh; Wael Sheet Hussein; Ali Fawzi Al-Hussainy; Ashok Kumar Bishoyi; M. M. Rekha; Mayank Kundlas; V. Kavitha; Zafar Aminov; Sada Ghalib Taher; Mariem Alwan; Mahmood Jawad; Hiba Mushtaq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Kangayam and Tharparkar cattle exhibit higher duplications in innate immune genes compared to Sahiwal, Gir, Karan Fries, and Holstein Friesian: insights from an array comparative genomic hybridization - Mayank Roshan; Ashutosh Vats; Kamlesh Kumari Bajwa; Sanjay Sharma; Menaka Thambiraja; Monika Sodhi; Dheer Singh; Ragothaman M. Yennamalli; Suneel Kumar Onteru (Mammalian Genome, 2025)

Unraveling the genetic diversity, population structure, and stability for yield-related traits of rice genotypes in mid-hills of northeastern India - Riya Raj; Amit Kumar; Balakrishnan C.; Simardeep Kaur; Veerendra Kumar Verma; Mayank Rai; S. P. Das; Vinay Kumar Mishra (Journal of Applied Genetics, 2025)

Epigenetic and Mitochondrial Metabolic Dysfunction in Multiple Sclerosis: A Review of Herbal Drug Approaches and Current Clinical Trials - Ashwani; Anjali Sharma; Mayank Kumar Choudhary; Dalapathi Gugulothu; Deepti Pandita; Surajpal Verma; Lalitkumar K. Vora; Dharmendra Kumar Khatri; Debapriya Garabadu (Molecular Neurobiology, 2025)
Multiple sclerosis (MS) is a complex autoimmune disease characterised by inflammation, demyelination, and neurodegeneration within the central nervous system (CNS). While the exact causes remain unclear, recent research highlights the significant role of epigenetic modifications and mitochondrial dysfunction in the disease’s onset and progression. Epigenetic alterations, such as DNA methylation, histone modification, and microRNA regulation, influence gene expression without altering the DNA sequence, leading to immune dysregulation and inflammation. Similarly, mitochondrial dysfunction, marked by impaired oxidative phosphorylation, reduced adenosine triphosphate (ATP) production, and increased reactive oxygen species (ROS), contributes to neurodegeneration and impaired remyelination in MS. The growing interest in targeting these two interconnected mechanisms has opened new avenues for MS treatment. Herbal drugs, known for their multi-targeted effects, have shown potential in modulating epigenetic markers and enhancing mitochondrial function. Compounds such as resveratrol, curcumin, epigallocatechin-3-gallate (EGCG), quercetin, and omega-3 fatty acids demonstrate potential in regulating DNA methylation, histone deacetylation, and mitochondrial biogenesis. These natural agents offer dual-action therapies by reducing oxidative stress and inflammation while promoting neuronal survival and remyelination. This review explores the therapeutic potential of herbal drugs targeting epigenetic and mitochondrial pathways in MS, evaluating their mechanisms of action and highlighting their promise as novel therapeutic agents. While initial findings are encouraging, further research and clinical trials are required to validate the efficacy of these herbal treatments and fully understand their potential in slowing disease progression and improving patient outcomes in MS. Such exploration could pave the way for safer, multi-targeted therapies, offering new hope in the management of MS and other neurodegenerative diseases.

Performance analysis of soil-geopolymer deep mix column in soft soil under static and cyclic loading - Sanjoli Gupta; Suresh Kumar; N. Muni Pradeep; Mayank Nishant (Soil Dynamics and Earthquake Engineering, 2025)

Isolates of Enterococcus faecalis from freshwater fish being sold in the retail fish markets harbor significantly higher antimicrobial resistance compared to isolates from fish farms - Anil Kumar; Arti Dwivedi; Mayank Soni; Vikash Sahu; Mohd Imran; Chandra Bhushan Kumar; Gaurav Rathore; Uttam Kumar Sarkar (Biologia, 2025)

STDdb-A curated database for sexually transmitted diseases - Krishnendu Barik; Mayank Kumar; Praffulla Kumar Arya; Anil Kumar (Next Research, 2025)

Understanding the linkages between seasonal variability and annual trends in groundwater levels in alluvial aquifers of Uttar Pradesh, India - Om Jee; Lalit Kumar Choudhary; Mayank Katiyar; Tushar Apurv (Journal of Hydrology, 2025)

Irrigation water quality prognostication: An innovative ensemble architecture leveraging deep learning and machine learning for enhanced SAR and ESP estimation in the east coast of India - Alok Kumar Pati; Alok Ranjan Tripathy; Debabrata Nandi; Rakesh Ranjan Thakur; Mayank Pandey (Journal of Environmental Chemical Engineering, 2025)

Impact of indoor plant-induced relative humidity on PM concentration in indoor urban environment - Supreet Kaur; Sumit Kumar Mishra; Vikas Goel; Mayank Kumar; Rishabh Singh; Mamta Devi; Harish Chandra; Vijayan Narayanasamy; S.P. Singh; Parag Sharma; Prashant Kumar (Atmospheric Pollution Research, 2025)

Assessment of Genetic Variability in Job’s Tears (Coix lacryma-jobi L.) Germplasm from Indian NEH Region Using Morpho-physiological Traits and SSR Markers - Avinash Pandey; Bharati Lap; Chubasenla Aochen; Amit Kumar; Wricha Tyagi; Mayank Rai (Plant Molecular Biology Reporter, 2025)

Biodistribution Studies of FITC Labelled DP1 and DP1 Encapsulated Coumarin-6 PLGA Nanoparticles in Murine Model - Satvika Sharma; Mahima Chugh; Sheetal Sharma; Mayank Maan; Devinder Kumar Dhawan; Avneet Saini (International Journal of Peptide Research and Therapeutics, 2025)

Groundwater quality assessment using water quality indices, hydrogeochemical studies and multivariate statistical analysis in Udham Singh Nagar district, Uttarakhand, India - Mayank Singh Bisht; Shiv Kumar; Narendra Kumar Goel; Manohar Arora; Velpuri Manikanta (Environment, Development and Sustainability, 2025)

Metabolomic Biomarkers for Prognosis in Non-Muscle Invasive Bladder Cancer: A Comprehensive Systematic Review and Meta-Analysis - Vishwajeet Singh; Mukul Kumar Singh; Anil Kumar; Dinesh Kumar Sahu; Mayank Jain; Anuj Kumar Pandey; Mantasha; Shubhendu Singh; Ajay Kumar Verma (Indian Journal of Clinical Biochemistry, 2025)

Distilled waste (Mentha) derived biochar for immobilization of chlorpyrifos in soil: Adsorption, leaching, and dissipation in two contrasting mesosphere - Mayank Singh; Santosh Kumar Yadav; Disha Mishra; Mohd. Ahsan; Puja Khare (Environmental Sustainability, 2025)

Intraseasonal variability of monsoon extremes and its impact on Kharif crops in the Western Plains and Kachchh Peninsula agroecological region of India - Devi Lal; Rinku Kumar; Ishtiaq Ahmed; Manoranjan Mishra; Mayank Shekhar; Chidanand Patil; Celso Augusto Guimarães Santos; Pritam Chand (Theoretical and Applied Climatology, 2025)

Exploring genetic diversity, population structure and stability for yield related traits in rice germplasm of northeastern India - C. Balakrishnan; Amit Kumar; Riya Raj; Veerendra Kumar Verma; Letngam Touthang; Rahul Kumar; Mayank Rai; S. P. Das; Vinay Kumar Mishra (Genetic Resources and Crop Evolution, 2025)

Unveiling PM2.5 sources: Double and tracer conjugate PMF approaches for high-resolution organic, BC, and inorganic PM2.5 data - Mohd Faisal; Umer Ali; Ajit Kumar; Mayank Kumar; Vikram Singh (Atmospheric Environment, 2025)

Chitosan nanoparticles of imatinib mesylate coated with TPGS for the treatment of colon cancer: In-vivo & in-vitro studies - Darshan Bhirud; Sankha Bhattacharya; Harshvardhan Raval; Preeti Chidambar Sangave; Girdhari Lal Gupta; Gaurav Paraskar; Megha Jha; Satyam Sharma; Sateesh Belemkar; Devendra Kumar; Rahul Maheshwari; Mayank Sharma (Carbohydrate Polymers, 2025)

Dynamically triggered events in mining- and monsoon-induced regions of Northwestern Deccan volcanic province of India - Mayank Dixit; Abhey Ram Bansal; M. Ravi Kumar; Rajat Pasricha (Natural Hazards, 2025)

Two different approaches for source apportionment of ambient black carbon in highly polluted environments - Ajit Kumar; Vikas Goel; Mohd Faisal; Umer Ali; Rakesh Maity; Dilip Ganguly; Vikram Singh; Mayank Kumar (Atmospheric Environment, 2024)

Revealing the Novel Genetic Resources for Blast Resistance in Diverse Rice Landraces of North-Eastern Hills of Himalayas - Riya Raj; Amit Kumar; Balakrishnan C; Philanim W. S; Letngam Touthang; S. P. Das; Mayank Rai; Veerendra Kumar Verma; Vinay Kumar Mishra (Plant Molecular Biology Reporter, 2024)

Multi-omics analysis reveals the positive impact of differential chloroplast activity during in vitro regeneration of barley - Parul Sirohi; Chanderkant Chaudhary; Mayank Sharma; Ravi Bodampalli Anjanappa; Suchi Baliyan; Ritika Vishnoi; Sumit Kumar Mishra; Reeku Chaudhary; Bhairavnath Waghmode; Anuj Kumar Poonia; Hugo Germain; Debabrata Sircar; et al. (Plant Molecular Biology, 2024)

Assessment of Active Deformation in the Surrounding Regions of the 7th to 12th AD Monuments in the Central Kumaon Himalayas: A Seismotectonic Approach using PSInSAR - Girish Ch. Kothyari; Achla Joshi; Rakesh K. Dumka; Bahadur S. Kotlia; Atul Kumar Patidar; Moulishree Joshi; Khayingshing Luirei; Sambit Prasanajit Naik; Ajay K. Taloor; Mayank Joshi; Hem Ch. Kothyari (Geoheritage, 2024)

Whole-body exposure to filtered fraction of diesel exhaust induced localized testicular damage through attenuated functional response of glutathione-s-transferase in adult male Wistar rats - Swarnabha Sarkar; Aditya Dontham; Ravindran Revand; Abhishek Kandpal; Debabrata Dasgupta; Bahni Ray; Mayank Kumar; Asmita Patil (Reproductive Toxicology, 2024)

An efficient one-pot synthesis and docking studies of bioactive new antiproliferative dispiro[oxindole/acenaphthylenone‒benzofuranone] pyrrolidine scaffolds - Tushar R. Sutariya; Gaurangkumar C. Brahmbhatt; Hiralben D. Atara; Narsidas J. Parmar; RajniKant; Vivek K. Gupta; Irene Lagunes; José M. Padrón; Prashant R. Murumkar; Mayank Kumar Sharma; Mange Ram Yadav (Molecular Diversity, 2024)

Unraveling metabolic pathways and key genes in Alzheimer’s, type 2 diabetes, and estrogen dysregulation among aging women: a systems biology approach - Mayank Roy Chowdhury; Vinith Kumar; Vijaykumar Sudarshana Deepa (Journal of Proteins and Proteomics, 2024)

Millennial to centennial-scale climate oscillations since 15000 cal yrs BP from Kanwar wetland in the Central Ganga Plain, India - Binita Phartiyal; Arvind Tiwari; Masud Kawsar; Manoj M.C; Mayank Shekhar; S. Nawaz Ali; Ravi Bhushan; Rujal R. Pachchigar; Anurag Kumar; Prasanna K; Anupam Sharma (Quaternary Science Reviews, 2024)

Bioaerosol emissions from wastewater treatment process at urban environment and potential health impacts - Yogesh Kumar Vishwakarma; Mayank; Kirpa Ram; Mukunda M. Gogoi; Tirthankar Banerjee; R.S. Singh (Journal of Environmental Management, 2024)

Study of secondary organic aerosol formation and aging using ambient air in an oxidation flow reactor during high pollution events over Delhi - Vikas Goel; Nidhi Tripathi; Mansi Gupta; Lokesh Kumar Sahu; Vikram Singh; Mayank Kumar (Environmental Research, 2024)

Festive fireworks in Delhi: A major source of elemental aerosols established through dispersion normalized PMF in a multiyear study - Mohd Faisal; Umer Ali; Ajit Kumar; Naba Hazarika; Vikram Singh; Mayank Kumar (Atmospheric Environment, 2024)

Cancer cell plasticity: from cellular, molecular, and genetic mechanisms to tumor heterogeneity and drug resistance - Gh Rasool Bhat; Itty Sethi; Hana Q. Sadida; Bilal Rah; Rashid Mir; Naseh Algehainy; Ibrahim Altedlawi Albalawi; Tariq Masoodi; Gowtham Kumar Subbaraj; Farrukh Jamal; Mayank Singh; Rakesh Kumar; et al. (Cancer and Metastasis Reviews, 2024)
Cancer is a complex disease displaying a variety of cell states and phenotypes. This diversity, known as cancer cell plasticity, confers cancer cells the ability to change in response to their environment, leading to increased tumor diversity and drug resistance. This review explores the intricate landscape of cancer cell plasticity, offering a deep dive into the cellular, molecular, and genetic mechanisms that underlie this phenomenon. Cancer cell plasticity is intertwined with processes such as epithelial-mesenchymal transition and the acquisition of stem cell–like features. These processes are pivotal in the development and progression of tumors, contributing to the multifaceted nature of cancer and the challenges associated with its treatment. Despite significant advancements in targeted therapies, cancer cell adaptability and subsequent therapy-induced resistance remain persistent obstacles in achieving consistent, successful cancer treatment outcomes. Our review delves into the array of mechanisms cancer cells exploit to maintain plasticity, including epigenetic modifications, alterations in signaling pathways, and environmental interactions. We discuss strategies to counteract cancer cell plasticity, such as targeting specific cellular pathways and employing combination therapies. These strategies promise to enhance the efficacy of cancer treatments and mitigate therapy resistance. In conclusion, this review offers a holistic, detailed exploration of cancer cell plasticity, aiming to bolster the understanding and approach toward tackling the challenges posed by tumor heterogeneity and drug resistance. As articulated in this review, the delineation of cellular, molecular, and genetic mechanisms underlying tumor heterogeneity and drug resistance seeks to contribute substantially to the progress in cancer therapeutics and the advancement of precision medicine, ultimately enhancing the prospects for effective cancer treatment and patient outcomes.

Can graphene-based composites and membranes solve current water purification challenges - a comprehensive review - Chetna Tewari; Gaurav Tatrari; Sumit Kumar; Mayank Pathak; Kundan Singh Rawat; Young Nam Kim; Biswajit Saha; Yong Chae Jung; Prithu Mukhopadhyay; Nanda Gopal Sahoo (Desalination, 2023)

PM2.5 air pollution prediction through deep learning using meteorological, vehicular, and emission data: A case study of New Delhi, India - Deepti Shakya; Vishal Deshpande; Manish Kumar Goyal; Mayank Agarwal (Journal of Cleaner Production, 2023)

Application of nano formulations in agriculture - Mayank Bhaskar; Aanand Kumar; Radha Rani (Biocatalysis and Agricultural Biotechnology, 2023)

Source apportionment, health risk assessment, and trajectory analysis of black carbon and light absorption properties of black and brown carbon in Delhi, India - Vikas Goel; Srishti Jain; Vikram Singh; Mayank Kumar (Environmental Science and Pollution Research, 2023)

Dual metal ion (Fe3+ and As3+) sensing and cell bioimaging using fluorescent carbon quantum dots synthesised from Cynodon dactylon - Sweta Gurung; Neha; Nimmala Arun; Mayank Joshi; Tanya Jaiswal; Anand P. Pathak; Parimal Das; Amaresh Kumar Singh; Ajay Tripathi; Archana Tiwari (Chemosphere, 2023)

An economic and sustainable approach to transform aluminosilicate-rich solid waste to functionally graded composite foam for high-temperature applications - Vaibhav Pandey; Mayank Kumar Yadav; S.K. Panda; V.K. Singh (Chemosphere, 2023)

Highly water permeable ‘reverse osmosis’ polyamide membrane of folded nanoscale film morphology - Utpal G. Thummar; J. Jayalakshmi; Mayank Saxena; Yogesh Suva; Nayan Nandha; Pranay Kumar; Vinod K. Aswal; Puyam S. Singh (Journal of Water Process Engineering, 2023)

Flame structure and stability for oxygen enhanced non-premixed combustion of highly diluted methane with helium and nitrogen - Anurag Mishra; Pushan Sharma; Mayank Kumar; Anjan Ray (Fuel, 2023)

First report of whole genome sequence of septicemic Pasteurella multocida serovar B:2 ‘Soron’ strain isolated from swine - Harshit Verma; Mayank Rawat; Rishendra Verma; Ravi Gandham; Ashok Kumar Tiwari; Raja Ishaq Nabi Khan; Manas Ranjan Praharaj; Emily Smith (Brazilian Journal of Microbiology, 2023)

Wild sesame (Sesamum prostratum Retz.) as potent source of salt tolerance through better physiological and biochemical adaptation than cultivated sesame (Sesamum indicum L.) - Mayank R. Raiyani; Anuj Kumar Singh; Kapil Kumar Tiwari; Hitendra S. Bhadauria; S. D. Solanki; Sushmita Singh (Vegetos, 2023)

Spatiotemporal variability and health risk assessment of PM2.5 and NO2 over the Indo-Gangetic Plain: A three years long study (2019-21) - Vikas Goel; Ajit Kumar; Srishti Jain; Vikram Singh; Mayank Kumar (Environmental Monitoring and Assessment, 2023)

Understanding Alzheimer’s Disease by Targeting Gut Microbiota and Role of Heavy Metals: Insight from Novel Therapeutical Approach - Anjalee Bhratee; Mayank Kumar; Md Reyaz Alam; Piyush Anand; Shamsher Singh (Current Pharmacology Reports, 2023)

Effect of Metal-resistant PGPB on the Metal Uptake, Antioxidative Defense, Physiology, and Growth of Atriplex lentiformis (Torr.) S.Wats. in Soil Contaminated with Cadmium and Nickel - Harsh Kumar; Shumailah Ishtiyaq; Paulo J. C. Favas; Mayank Varun; Manoj S. Paul (Journal of Plant Growth Regulation, 2023)

Analysis of aerosol liquid water content and its role in visibility reduction in Delhi - Umer Ali; Mohd Faisal; Dilip Ganguly; Mayank Kumar; Vikram Singh (Science of The Total Environment, 2023)

Concepts of circular economy for sustainable management of electronic wastes: challenges and management options - Arun Lal Srivastav; Markandeya; Naveen Patel; Mayank Pandey; Ashutosh Kumar Pandey; Ashutosh Kumar Dubey; Abhishek Kumar; Abhishek Kumar Bhardwaj; Vinod Kumar Chaudhary (Environmental Science and Pollution Research, 2023)

Molecular characterization of carbapenem resistant E. coli of fish origin reveals the dissemination of NDM-5 in freshwater aquaculture environment by the high risk clone ST167 and ST361 - Arti Dwivedi; Chandra Bhushan Kumar; Anil Kumar; Mayank Soni; Vikash Sahu; Abhishek Awasthi; Gaurav Rathore (Environmental Science and Pollution Research, 2023)

Estimation of time dependent scour depth around circular bridge piers: Application of ensemble machine learning methods - Sanjit Kumar; Manish Kumar Goyal; Vishal Deshpande; Mayank Agarwal (Ocean Engineering, 2023)

Last 10 millennial history of Indian summer monsoon in the Bengal region – a multi-proxy reconstruction from a lacustrine archive - Ruby Ghosh; Korobi Saikia; Oindrila Biswas; Shailesh Agrawal; P. Morthekai; Mohammad Arif; Binita Phartiyal; Anupam Sharma; Neha Singh; Dipak Kumar Paruya; Pyarimohan Maharana; Mayank Shekhar; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Spatio-temporal variation of C-PM2.5 (composition based PM2.5) sources using PMF*PMF (double-PMF) and single-combined PMF technique on real-time non-refractory, BC and elemental measurements during post-monsoon and winter at two sites in Delhi, India - Ashutosh Kumar Shukla; Sachchida Nand Tripathi; Francesco Canonaco; Vipul Lalchandani; Ravi Sahu; Deepchandra Srivastava; Jay Dave; Navaneeth Meena Thamban; Sreenivas Gaddamidi; Lokesh Sahu; Mayank Kumar; Vikram Singh; et al. (Atmospheric Environment, 2023)

Interaction of Antioxidant Trace Minerals Affecting Blood Picture Including Antioxidant Profile of Healthy Buffalo (Bubalus bubalis) Calves - Vishal Mudgal; Anil Kumar Garg; Ram Sharan Dass; Mayank Rawat (Biological Trace Element Research, 2023)

Application of novel hybrid machine learning techniques for particle Froude number estimation in sewer pipes - Sanjit Kumar; Bablu Kirar; Mayank Agarwal; Vishal Deshpande (Natural Hazards, 2022)

Applications of CRISPR/Cas technology against drug-resistant lung cancers: an update - Mayank Chaudhary; Pooja Sharma; Tapan Kumar Mukherjee (Molecular Biology Reports, 2022)

Spatial analysis of soil quality using geospatial techniques in Botanic Garden of Indian Republic, Noida, Uttar Pradesh, India - Deepakshi Babbar; Sandeep Kr. Chauhan; Damini Sharma; Kusum Upadhyay; Mayank D. Dwivedi; Mehebub Sahana; Shailender Kumar (Environmental Sustainability, 2022)
Ex-situ conservation places such as botanical gardens require sufficient soil quality to support introduced species from various phytogeographical zones. The soil quality of the Botanic Garden of Indian Republic (BGIR), Noida, Uttar Pradesh, was evaluated to quantify soil nutrients. The dependency of one nutrient on the other nutrients was investigated using Pearson correlation and Multilinear regression analysis (MLRA). At the 0.05 level of significance, the nutrients Log10S and Log10EC ( r = 0.97), N and OC ( r = 0.98), Mn and OC ( r = 0.97), Mn and N ( r = 0.92), Ca and pH ( r = − 0.91), Cu and Fe ( r = 0.94) were found to be associated. Correspondence Analysis (C.A.) has been performed to find the association of soil elements with the soil type of study site. The spatial indices like NDVI (Normalized Difference Vegetation Index), EVI2 (Enhanced Vegetation Index), ARVI (Atmospherically Resistant Vegetation Index), NPCRI (Normalized Pigment Chlorophyll Index), RDVI (Renormalized Difference Vegetation Index) have shown significant correlation with the Log 10 S, Mg, Log 10 Zn, B and Fe respectively (with respective Pearson correlation coefficient r = 0.88, r = − 0.90, r = − 0.93, r = 0.91, r = 0.92 at P < 0.05). ARVI, along with other indices SCI (Soil Composition Index), NDMI (Normalized Difference Moisture Index), and MSAVI (Modified Soil Adjusted Vegetation Index), are also the predictor variables for Log 10 Zn ( r = − 0.89, r = − 0.88 r = 0.92 at P < 0.05 respectively). MAVI2 (Moisture Adjusted Vegetation Index) positively correlates with OC, Mn content ( r = 0.91, r = 0.93 respectively). MSAVI is negatively interrelated with Ca ( r = − 0.89), SCI is negatively interrelated with Log 10 K ( r = − 0.98), BSI (Bare Soil Index) is positively associated with pH ( r = 0.91), and negatively with Ca ( r = − 0.93). At the same time, other indices like SAVI (Soil Adjusted Vegetation Index), SATVI (Soil Adjusted Total Vegetation Index), NDWI (Normalized Difference Water Index), and DVI (Difference Vegetation Index) have failed to explain the presence of soil nutrients based on spectral reflectance. This study is important for understanding the changing nutrient status of soil at the conservation site for successfully establishing plants from different phytogeographical zones.

Predicting the distributional range shifts of Rhizocarpon geographicum (L.) DC. in Indian Himalayan Region under future climate scenarios - Devendra Kumar; Aseesh Pandey; Sandeep Rawat; Mayank Joshi; Rajesh Bajpai; Dalip Kumar Upreti; Surendra Pratap Singh (Environmental Science and Pollution Research, 2022)

Thermal neutron as a potential mutagen for induced plant mutation breeding: radiosensitivity response on wheat and rice - Shivdas Tukaram Kadam; Gautam Vishwakarma; Yogesh Kashyap; Mayank Shukla; Tushar Roy; Parmeshwar Kumar Sahu; Deepak Sharma; Abhijit Shaligram Shitre; Vikash Kumar; Bikram Kishore Das (Genetic Resources and Crop Evolution, 2022)

Experimental investigation and comparative machine learning prediction of the compressive strength of recycled aggregate concrete incorporated with fly ash, GGBS, and metakaolin - Uma Shankar Biswal; Mayank Mishra; Manav Kumar Singh; Dinakar Pasla (Innovative Infrastructure Solutions, 2022)

Phylogenetic relationships in Indian Daphne (Thymelaeaceae) based on nuclear ITS and cpDNAdata - Arnab Banerjee; Mayank D. Dwivedi; Shruti Kasana; Paramjit Singh; Vikas Kumar; Debabrata Maity; Arun K. Pandey (Biologia, 2022)

CRISPR/Cas technology for improving nutritional values in the agricultural sector: an update - Mayank Chaudhary; Tapan Kumar Mukherjee; Raj Singh; Mahiti Gupta; Soniya Goyal; Paavan Singhal; Rakesh Kumar; Nabin Bhusal; Pooja Sharma (Molecular Biology Reports, 2022)

Association of severity and mortality of Covid-19 cases among acute kidney injury and sexual dimorphism - Mukul Kumar Singh; Mayank Jain; Hari Shyam; Dinesh Kumar Sahu; Archana Mishra; Pratap Shankar; Shailendra Kumar; Vishwajeet Singh (Molecular Biology Reports, 2022)

Anti-inflammatory potential of cannabidiol (CBD) on combination of caecal slurry, LPS, and E. coli-induced systemic inflammatory response syndrome (SIRS) in Sprague Dawley Rats - Mahendra Kumar Trivedi; Sambhu Mondal; Mayank Gangwar; Snehasis Jana (Inflammopharmacology, 2022)

Associated pathogenesis of bladder cancer and SARS-CoV-2 infection: a treatment strategy - Mukul Kumar Singh; Mayank Jain; Hari Shyam; Pratap Shankar; Vishwajeet Singh (VirusDisease, 2021)

Effect of montmorillonite nanoclay and sulphur-modified blends on the properties of bituminous mixes - Adheesh kumar vivek; Mayank Sukhija; Khwairakpam Lakshman Singh (Innovative Infrastructure Solutions, 2021)

Statistical analysis of high-resolution mesoscale meteorology derived from weather research and forecasting model - Awkash Kumar; Shraddha Dhakhwa; Mayank Kumar (Modeling Earth Systems and Environment, 2021)

Diarylidenecyclopentanone derivatives as potent anti-inflammatory and anticancer agents - Nitesh Tamang; Gayathri Ramamoorthy; Mayank Joshi; Angshuman Roy Choudury; Siva Kumar B.; Nageswara Rao Golakoti; Mukesh Doble (Medicinal Chemistry Research, 2020)

Palaeoredox link with the late Neoproterozoic–early Cambrian Bilara carbonate deposition, Marwar Supergroup, India - A. H. Ansari; S. K. Pandey; Kamlesh Kumar; Shailesh Agrawal; Shamim Ahmad; Mayank Shekhar (Carbonates and Evaporites, 2020)

Experimental evaluation of the behaviour of bamboo-reinforced beam–column joints - Mayank Mishra; M. Kranti Kumar; Damodar Maity (Innovative Infrastructure Solutions, 2019)

Evaluation and correlation of oxidative stress and haemato-biochemical observations in horses with natural patent and latent trypanosomosis in Punjab state of India - Rahul Parashar; Lachhman Das Singla; Mayank Gupta; Suresh Kumar Sharma (Acta Parasitologica, 2018)
The haemato-biochemical indices and oxidative stress markers in horses naturally infected with Trypanosoma evansi were evaluated by analyzing the level of these parameters between T. evansi infected (microscopically positive patent group and PCR positive latent group) and infection free horses. To compare the hemato-biochemical indices and oxidative stress indicators, horses were divided into three categories based on diagnostic test employed and positive results obtained. These included Romanowsky stained slide positive group (Group I; n = 6), PCR positive group (group II; n = 28) and negative control group (group III, n = 30), revealing parasitologically positive patent, molecular positive latent and disease free status of horses. A significant reductions in total erythrocytes count (TEC, P = 0.01), haemoglobin (Hb, P = 0.01) and packed cell volume (PCV, P = 0.04) was noticed both in group I and group II while significant neutrophilia and lymphocytopenia was observed in group I when compared to negative control group. Substantial increase in creatinine (CRTN, P = 0.032) and gamma glutamyl transferase (GGT, P = 0.012) in group I while significant decrease in glucose (GLU, P = 0.04) and iron (Fe, P = 0.01) were noticed in both group I and group II in comparison to group III. A significant difference in lipid peroxides (LPO, P = 0.01) with highest level in patent group I (15.33 ± 0.53) followed by PCR positive latent group (14.09 ± 1.66) indicates higher lipid peroxidation in erythrocytes and oxidative stress in decreasing order when compared with infection free control horses (9.83 ± 0.97). Catalase (CAT, P = 0.01) was significantly lower in parasitological (0.82 ± 0.14) and molecular positive cases (1.27 ± 0.35) in comparison to control group (3.43 ± 0.96). The levels of superoxide dismutase (SOD, P = 0.01), reduced glutathione (GSH, P = 0.01) and ferric reducing antioxidant power (FRAP, P = 0.01) were significantly lower in parasito-molecular positive cases as compared to infection free control horses. An inverse correlation of RBC count with LPO and GSH and a direct correlation with catalase, SOD and FRAP was revealed. Overall, the observed substantial decreases in the oxidative parameters like catalase CAT, SOD, GSH and FRAP activities with remarkably elevated levels of LPO indicate high exposure of erythrocytes to oxidative damage in T.evansi infected horses.

Association of Toll like receptor 2 and 9 gene variants with pulmonary tuberculosis: exploration in a northern Indian population - Mayank Mittal; Sanjay Kumar Biswas; Vandana Singh; Nidhi Arela; Vishwa Mohan Katoch; Ram Das; Virendra Singh Yadav; Bharat Bajaj; Keshar Kunja Mohanty (Molecular Biology Reports, 2018)

Role of Vital Trace Elements in Nanocurcumin-Centered Formulation: A Novel Approach to Resuscitate the Immune System - Mahendra Kumar Trivedi; Mayank Gangwar; Sambhu Charan Mondal; Snehasis Jana (Biological Trace Element Research, 2018)

Immunomodulatory potential of nanocurcumin-based formulation - Mahendra Kumar Trivedi; Sambhu Charan Mondal; Mayank Gangwar; Snehasis Jana (Inflammopharmacology, 2017)

One-pot synthesis, biological evaluation, and docking study of new chromeno-annulated thiopyrano[2,3-c]pyrazoles - Bhagyashri D. Parmar; Tushar R. Sutariya; Gaurangkumar C. Brahmbhatt; Narsidas J. Parmar; Rajni Kant; Vivek K. Gupta; Prashant R. Murumkar; Mayank Kumar Sharma; Mange Ram Yadav (Molecular Diversity, 2016)

Detection of Peste Des Petits Ruminants Virus (PPRV) Genome from Nasal Swabs of Dogs - Barkha Ratta; Mayank Pokhriyal; Shanker K. Singh; Ajay Kumar; Meeta Saxena; Bhaskar Sharma (Current Microbiology, 2016)

Bovine Herpes Virus 1 Major Immediate Early Transcription Unit 1 (IETU-1) Uses Alternative Promoters to Transcribe BICP0 and BICP4 Transcripts - Mayank Pokhriyal; O. P. Verma; Barkha Ratta; Ajay Kumar; Meeta Saxena; Bhaskar Sharma (Current Microbiology, 2016)

Design, synthesis and mode of action of novel 2-(4-aminophenyl)benzothiazole derivatives bearing semicarbazone and thiosemicarbazone moiety as potent antimicrobial agents - Meenakshi Singh; Sudhir Kumar Singh; Mayank Gangwar; Gopal Nath; Sushil K. Singh (Medicinal Chemistry Research, 2016)

Exploring structural requirements for peripherally acting 1,5-diaryl pyrazole-containing cannabinoid 1 receptor antagonists for the treatment of obesity - Mayank Kumar Sharma; Prashant R. Murumkar; Rajani Giridhar; Mange Ram Yadav (Molecular Diversity, 2015)

Abutilon indicum L.: a prospective weed for phytoremediation - Mayank Varun; Disha Jaggi; Rohan D’Souza; Manoj S. Paul; Bhumesh Kumar (Environmental Monitoring and Assessment, 2015)

Virtual screening-based identification of lead molecules as selective TACE inhibitors - Prashant R. Murumkar; Mayank Kumar Sharma; Rajani Giridhar; Mange Ram Yadav (Medicinal Chemistry Research, 2015)

Structural requirements for imidazo[1,2-a]pyrazine derivatives as Aurora A kinase inhibitors and validation of the model - Ashish M. Kanhed; Vishal P. Zambre; Vijay A. Pawar; Mayank Kumar Sharma; Rajani Giridhar; Mange Ram Yadav (Medicinal Chemistry Research, 2014)

In vitro antimicrobial activity of o-phenylenediamine-tert-butyl-N-1,2,3-triazole carbamate analogs - Manavendra Kumar Singh; Mayank Gangwar; Dharmendra Kumar; Ragini Tilak; Gopal Nath; Alka Agarwal (Medicinal Chemistry Research, 2014)

Three-dimensional quantitative structure–activity relationship CoMFA/CoMSIA on pyrrolidine-based tartrate diamides as TACE inhibitors - Prashant R. Murumkar; Mayank Kumar Sharma; Anurag C. Shinde; Kailash G. Bothara (Medicinal Chemistry Research, 2013)

Genotypic characterization of dengue virus strains circulating during 2007-2009 in New Delhi - Anita Chakravarti; Mayank Singh Chauhan; Suman Kumar; Anzar Ashraf (Archives of Virology, 2013)

Bioassay as monitoring system for lead phytoremediation through Crinum asiaticum L. - Mayank Varun; Rohan D’Souza; Devendra Kumar; Manoj S. Paul (Environmental Monitoring and Assessment, 2011)

Expression of GRP and its receptor is associated with improved survival in patients with colon cancer - Claudio A. Rivera; Ned C. Ahlberg; Lauren Taglia; Mayank Kumar; Adam Blunier; Richard V. Benya (Clinical & Experimental Metastasis, 2009)

Electrocoagulation Studies on Treatment of Biodigester Effluent using Aluminum Electrodes - F. Infant Anto Ponselvan; Mayank Kumar; Jodha Ram Malviya; Vimal Chandra Srivastava; Indra Deo Mall (Water, Air, & Soil Pollution, 2009)